Miscantus productivity depending on the area of food in the condition of the western Forest-Steppe - Osadchuk, V.; Semenchuk, V.; Gunchak, T.; SandulyakТ. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
In the article, the research results on miscanthus productivity according to its nutrition area are set out. It is established, that the highest miscanthus yield forms at using the planting scheme 3 rhizomes per 1 linear meter running of a row, with a row spacing width 0.7 m. In condition of perceptible decrease of precipitation quantity and steady increase of air temperature, no significant effect of plants foliar fertilization with a micro-fertilizer «Avatar 1» in the planting phase has been established on miscanthus productivity.